A prova do fato jurídico tributário - Martins, André Felipe Saide (2007)
This paper examines the evidence of the tax legal fact. To such purpose, the first chapter studies the characteristics of the tax legal fact as a type of legal fact. Considering that Law only exists when language is present, i.e., Law only exists when it can be translated into competent language, by means of evidence; it was indispensable to insert elements of Legal Philosophy. As a sequence, in the field of General Law Theory, the fact is qualified as a legal fact and then is classified. Following, the role of general and abstract rule of law is explained, as well as the role of individual and concrete rule of law in the formation of the tax legal fact. In order to obtain an adequate treatment for the legal analysis of the evidence, in the second chapter matters that are directly related to the evidence of a tax legal fact were selected. The concept of evidence was identified, and the sense of the word truth for Law was interpreted, as well as defining the evidence proceeding, without forgetting the means of evidence. It was necessary for the researcher to study in detail the evidence of the tax legal fact. To be coherent with the premises established in the first two chapters, without which the third could not be developed, the researcher tried to answer the main questions about the matter, mainly regarding how to prove the tax legal fact, extracting conclusions based on the fundamental principles of the Federal Constitution, in compliance to the jurisprudence adopted by administrative and judicial entities